Pembimbingan Perintisan Sekolah Islam Terpadu di Yayasan Fadilaturrahman Ibnu Masud, Labuhan Haji, Lombok Timur - Affan; Al-Qoyyim, Thufail Mujaddid; Muharrik, Burhan Al (Universitas Mataram, 2024)
Education is the main foundation for the progress of a nation. In Indonesia, efforts to improve the quality of education continue to be made, especially in underdeveloped areas. One important initiative is the establishment of integrated Islamic schools that not only focus on academic aspects but also the development of Islamic character and values. The Fadilaturrahman Ibnu Masud Foundation in East Lombok is active in this effort through mentoring and outreach activities aimed at increasing teachers' knowledge and skills in starting quality elementary schools and kindergartens. This research aims to evaluate the mentoring activities carried out by the foundation to improve the abilities of local teachers. The research method used was descriptive qualitative with a sample of 12 teachers who had taken part in mentoring activities. Data was collected through an in-depth evaluation questionnaire and then analyzed using descriptive statistics. The research results show that the Fadilaturrahman Ibnu Masud Foundation's mentoring activities succeeded in providing significant benefits for teachers. The majority of respondents considered the material presented to be very good and did not experience difficulty in understanding the material. Teachers gain essential knowledge about school management, curriculum development, and strengthening Islamic values. Apart from that, they also realize the importance of relationships with related agencies to support school pioneering. This research confirms the importance of mentoring and training for teachers, especially in remote areas, and provides a basis for the development of more effective mentoring programs in the future. It is hoped that the research results can contribute to improving the quality of education in Indonesia, especially in remote areas such as East Lombok.